2020
DOI: 10.21203/rs.3.rs-25105/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Nipple Repair in the Treatment of  Lactating Nipple Injury

Abstract: Objective To explore the effect of nipple repair in the treatment of lactating nipple injury.Methods Patients with nipple lesions admitted to the Maternal and Child Health Hospital of Haidian District from December 2015 to January 2020 were retrospective control study. The patients received nipple repair was the study group, the patients did not treated with medicine or surgery was the control group. Patients in both groups continued to be exclusively breastfeed with good sucking, The method of chi-square test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been observed that surface modification would render the pore volume in the GO/HNTs composite to improve the adsorbent capacity. 171−173 To address this challenge, a facile coprecipitation procedure was utilized to achieve Fe 3 O 4 /HNTs@rGO magnetic composites 174 (Scheme 44) without surface modification. Fe 3 O 4 nanoparticles could easily be adsorbed onto rGO and HNTs resulting in the formation of a nucleation center due to electrostatic interaction eliminating the electrostatic repulsion between negatively charged components.…”
Section: Adsorption/recognition Of Organic Componentsmentioning
confidence: 99%
“…It has been observed that surface modification would render the pore volume in the GO/HNTs composite to improve the adsorbent capacity. 171−173 To address this challenge, a facile coprecipitation procedure was utilized to achieve Fe 3 O 4 /HNTs@rGO magnetic composites 174 (Scheme 44) without surface modification. Fe 3 O 4 nanoparticles could easily be adsorbed onto rGO and HNTs resulting in the formation of a nucleation center due to electrostatic interaction eliminating the electrostatic repulsion between negatively charged components.…”
Section: Adsorption/recognition Of Organic Componentsmentioning
confidence: 99%